Implementation of green purchasing to support a The sustainable environment at Discovery Kartika Plaza Hotel - Ni Wayan Rismayanti; I Putu Astawa; I Nyoman Rajin Aryana; I Putu Budiarta; Cokorda Istri Sri Widhari (The Postgraduate School of Tourism Sahid Polytechnic, 2023)
Purpose: This research aims to discover the application of green purchasing in Discovery Kartika Plaza Hotel to support a sustainable environment. Research methods: This study uses a qualitative descriptive method through data reduction, data presentation, and conclusions and verification. The observation technique is used in collecting data, supported by interviews and document study. Results and discussion: The green purchasing program has been implemented correctly and by applicable rules and positively impacts the environment. Discovery Kartika Plaza Hotel will implement green purchasing; it will positively impact the surrounding environment and support a sustainable environment. Implication: Therefore, with the implementation of green purchasing, the environment around Discovery Kartika Plaza Hotel will be preserved and support a sustainable environment to meet the needs of living things in future generations. This research contributes to the science of green purchasing. Keywords: hotel, green purchasing, sustainable environment.